Descriptive study of HIV/AIDS-related stigma experienced by people living with HIV/AIDS (PLWHA) in healthcare settings offering family planning and/or HIV services in Kapiri-Mposhi, Zambia - Sinyangwe, George (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2012.